Mechanisms and therapeutic applications of β-cyclodextrin in drug solubilisation and delivery systems - Khatoon, Hena; Mohd Faudzi, Siti Munirah; Sohajda, Tamas (John Wiley and Sons, 2025)
Inadequate water solubility constrains the clinical efficacy of several therapeutic treatments, affecting around 40% of authorised drugs and up to 90% of investigational compounds under development. This study examines the efficacy of β-cyclodextrin (β-CD) and its principal derivatives, hydroxypropyl-β-cyclodextrin (HPβCD), sulfobutylether-β-cyclodextrin (SBEβCD) and methylated β-cyclodextrin (MEβCD), in enhancing drug solubility, absorption and therapeutic efficacy. β-CD enhances dissolution rates, disrupts drug crystallinity, alters particle size and facilitates controlled release via non-covalent inclusion complexes. These technologies improve oral bioavailability for hydrophobic and labile compounds while facilitating injectable and targeted medication delivery. Notable examples include RMβCD-enhancing ketoconazole, yielding a 2.2-fold increase in systemic exposure in vivo, while HPβCD markedly improved itraconazole solubility by 27-fold. In addition to solubility, β-CD platforms have evolved into nanosponges, polymeric carriers and metal–organic frameworks (MOFs), facilitating site-specific release and reducing toxicity. Therapeutic applications include a wide array of pharmacological classes, including antifungal, antibacterial, antiviral, anticancer, antioxidant, analgesic, and cardiovascular agents. Moreover, β-CD-functionalised molecularly imprinted polymers (MIPs) and essential oil complexes enhance their use in biotechnology, food safety and environmental domains. This research consolidates the existing evidence on the various mechanisms and translational possibilities of β-CD in contemporary drug delivery systems.